2014
DOI: 10.1016/j.drugalcdep.2014.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D3 receptor alterations in cocaine-dependent humans imaged with [11C](+)PHNO

Abstract: Background Evidence from animal models and postmortem human studies points to the importance of the dopamine D3 receptor (D3R) in cocaine dependence (CD). The objective of this pilot study was to use the D3R-preferring radioligand [11C](+)PHNO to compare receptor availability in groups with and without CD. Methods Ten medically healthy, non-treatment seeking CD subjects (mean age 41±8) in early abstinence were compared to 10 healthy control (HC) subjects (mean age 41±6) with no history of cocaine or illicit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
61
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 50 publications
(75 reference statements)
11
61
3
Order By: Relevance
“…Further work has investigated a selective D 3 -antagonist medication in an operant food self-administration paradigm and showed that a D 3 -antagonist attenuated lever presses and food intake in both lean and OB rats, providing preliminary evidence of D 3 R-related motivation to consume food (Thanos et al, 2008). This notion is consistent with clinical data implicating the D 3 R in populations abusing substances that influence nigrostriatal reward pathway function (Boileau et al, 2012;Erritzoe et al, 2014;Matuskey et al, 2014;Payer et al, 2014).…”
Section: Introductionsupporting
confidence: 69%
See 4 more Smart Citations
“…Further work has investigated a selective D 3 -antagonist medication in an operant food self-administration paradigm and showed that a D 3 -antagonist attenuated lever presses and food intake in both lean and OB rats, providing preliminary evidence of D 3 R-related motivation to consume food (Thanos et al, 2008). This notion is consistent with clinical data implicating the D 3 R in populations abusing substances that influence nigrostriatal reward pathway function (Boileau et al, 2012;Erritzoe et al, 2014;Matuskey et al, 2014;Payer et al, 2014).…”
Section: Introductionsupporting
confidence: 69%
“…Our data suggest that D 2/3 Rs are higher in OB compared with NW individuals in regions densely populated with D 3 Rs, thus implicating the D 3 R as a potential pharmacologic target for the treatment of obesity. These data also implicate the same nigrostriatal pathway alterations in obesity that have been previously observed with [ 11 C](+)PHNO in cocaine (Matuskey et al, 2014;Payer et al, 2014), methamphetamine (Boileau et al, 2012), and alcohol (Erritzoe et al, 2014) abusers, indicating excessive food consumption might alter reward pathways in similar ways as do substances of abuse. The direct role of the D 3 R in addiction is not currently clear .…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations